Multivariate analysis on students' cognitive assessment, attitude, and skill evaluation in problem-based learning - Santoso, Sabar; Pramesti, Getut (Department of Mathematics Education University of Muhammadiyah Malang, 2024)
To improve the quality of education, the Ministry of Education and Culture of the Republic of Indonesia designed the